Menopause versus aging: The predictor of obesity and metabolic aberrations among menopausal women of Karnataka, South India - Shruti Dasgupta; Mohammed Salman; S Lokesh; D Xaviour; S Yaseen Saheb; B V Ravi Prasad; Biswanath Sarkar (Wolters Kluwer Medknow Publications, 2012)
Context: Increased incidences of cardiovascular disorder and metabolic syndrome particularly after menopause have raised curiosity for the underlying factors. However, it is still a debate whether age or menopausal transition is a greater contributor. Aims: To elucidate the inter-relationships of age, menopause, and associated obesity and to assess their independent effects on aggravation of cardio metabolic risk factors in postmenopausal women. Settings and Design: Four hundred two women aged between 30 and 75 years were recruited in a cross-sectional study from Southern India. Three hundred sixteen participants exempting exclusion criteria, comprising of 169 premenopausal and 147 postmenopausal women were finally included. Materials and Methods: Anthropometric measurements such as weight, height, waist circumference (WC), hip circumference (HC), fat percentage, basal metabolic rate (BMR), and blood pressure were taken. Fasting plasma glucose, postprandial glucose, glycated hemoglobin (HbA1c), lipid profile, and C-reactive protein (CRP) were also measured. Statistical Analysis Used: Independent t-test, Analysis of covariates (ANCOVA), Pearson's correlation coefficients and multiple stepwise linear regression model analysis were done. Results: A significant increase in physical and metabolic factors was observed in postmenopausal women compared to premenopausal women except WC and HbA1c. Contrastingly, high-density lipoprotein cholesterol (HDL) levels and BMR were significantly decreased. After adjusting for BMI and age, the significant differences in the variables through the menopausal transition persisted, including an increase in WC. Significant correlation was observed between age and measures of general obesity such as BMI (P < 0.05) and fat percentage (P < 0.001) but not with central obesity indices. Menopausal status and WC exerted an independent effect on most of the metabolic risk factors (P < 0.001 or P < 0.01). Fat percentage was the predicting variable for CRP, HbA1c, diastolic blood pressure (P < 0.001), and HDL (P < 0.01). But Age showed independent effect only on HbA1c. Conclusions: Menopausal transition brings about anomalies in total body composition characterized by an increased body fat mass and central adiposity. This creates a compatible atmosphere for abnormal metabolism and aggravated cardio metabolic risk factors. Thus, menopausal status and associated obesity is the major predictor of metabolic aberrations over age in menopausal women.